The Efficacy of Honey Compared to Silver Sulfadiazine in Pediatric Burn Wound Dressing in Superficial and Partial Thickness Burns - Mahek, Lubna; Bashir, Afzaal; Shoukat, Zubair; Iqbal, Faryal; Talat, Nabila (Journal of Neonatal Surgery, 2025)
Background: Children often get burn injuries, with partial-thickness and superficial burns being the most common kind. Timely and effective wound management is essential to reduce complications, accelerate healing, and minimize scarring. Objectives: To compare the efficacy of honey versus silver sulfadiazine in dressing superficial and partial-thickness burns in pediatric patients. Study Design & Setting: This was a comparative interventional study conducted at the Paediatric surgery unit 1 the Children Hospital and University of Child Health Sciences Lahore from Feb 2024 to July 2024. Methodology: Children with burns that were either superficial or partial-thickness and involving less than 20% TBSA were divided into two equal groups. The patients' ages ranged from 1 to 12 years. Honey dressings were given to Group A, while 1% silver sulfadiazine dressings were given to Group B. Time to wound healing, discomfort during dressing changes, infection rates, and dressing changes were all factors that were evaluated in this study. The data were examined with SPSS version 25, and a significance level of p < 0.05 was deemed. Results: The honey group showed significantly faster wound healing (9.3 ± 2.1 vs. 13.7 ± 3.4 days; p < 0.001), lower pain scores, reduced infection rates (8.3% vs. 23.3%; p = 0.026), and fewer dressing changes compared to the SSD group. Conclusion: Compared to silver sulfadiazine, honey is superior for treating children's superficial and partial-thickness burns. It offers faster healing, better comfort, and reduced infection risk, making it a suitable alternative in pediatric burn care